Present and future medical applications of microbial exopolysaccharides - Moscovici, Misu (Frontiers in Microbiology, 2015)
Microbial exopolysaccharides (EPS) have found outstanding medical applications since the mid-twentieth century, with the first clinical trials on dextran solutions as plasma expanders. Other EPS entered medicine firstly as conventional pharmaceutical excipients (e.g., xanthan - as suspension stabilizer, or pullulan – in capsules and oral care products). Polysaccharides, initially obtained from plant or animal sources, became easily available for a wide range of applications, especially when they were commercially produced by microbial fermentation. Alginates are used as anti-reflux, dental impressions, or as matrix for tablets. Hyaluronic acid and derivatives are used in surgery, arthritis treatment or wound healing. Bacterial cellulose is applied in wound dressings or scaffolds for tissue engineering. The development of drug controlled-release systems and of micro- and nanoparticulated ones, has opened a new era of medical applications for biopolymers. EPS and their derivatives are well suited potentially non-toxic, biodegradable drug carriers. Such systems concern rating and targeting of controlled release. Their large area of applications is explained by the available manifold series of derivatives, whose useful properties can be thereby controlled. From matrix inclusion to conjugates, different systems have been designed to solubilize, and to assure stable transport in the body, target accumulation and variable rate-release of a drug substance. From controlled drug delivery, EPS potential applications expanded to vaccine adjuvants and diagnostic imaging systems. Other potential applications are related to the bioactive (immunomodulator, antitumor, antiviral) characteristics of EPS. The numerous potential applications still wait to be developed into commercial pharmaceuticals and medical devices. Based on previous and recent results in important medical-pharmaceutical domains, one can undoubtedly state that EPS medical applications have a broad future ahead.